An evaluation of surgical excision versus steroid injection for the management of ganglion cysts - Karpaka Vinayakam Gopalakrishnan; Kawushik Kumar Prabhakaran (Scientific Reports)
Abstract Ganglion cysts are benign soft tissue tumors that commonly occur in the joints, especially the wrist. Surgical excision and steroid injection are the two main treatment options; however, their efficacy remains unclear. This prospective interventional control trial included 54 patients with ganglion cysts treated between March 2023 and March 2024 at Saveetha Medical College Hospital, Chennai. Patients were divided into two groups: Group A underwent surgical excision and Group B received aspiration followed by 40 mg of intralesional triamcinolone acetonide injection. The highest incidence was observed in younger patients aged 14–19 years (13 patients), with more females (57.4%) affected. The cysts were equally distributed between the left and right hands. All patients presented with swelling, and 59.3% experienced pain/discomfort. In Group A surgical excision success rate was 92.5%, with a 7.5% recurrence rate. Group B had a lower success rate (64.3%) and higher recurrence rate (35.7%) with aspiration and injection. Surgical excision demonstrated significantly better outcomes, with higher success and lower recurrence rates than aspiration and steroid injection for the management of ganglion cysts. Therefore, this should be considered the preferred treatment option.